(untitled) (Latakia University Journal -Biological Sciences Series, 2017)
الهدف من هذا البحث, هو تبسيط طريقة الحصول على التبخر-نتح الكامن الذي يشكل سقفا" للاحتياجات المائية للمحاصيل, بالاعتماد على بعض الصيغ التجريبية وهي صيغة تورك (Turc,1967) وصيغة تورنويت (Thornthwaite, 1948) بالمقارنة مع صيغة بلاني كريدل المعدلة(Blaney_Criddle, 1950) والتي تعتبر الصيغة المرجع في هذا البحث, وإيجاد علاقة تمكننا من استعمال طريقة الأحواض المائية الحرة (حوض صنف آ) كدليل نسبي للحاجة إلى الري في منطقة اللاذقية بمقارنته مع قيم التبخر-نتح الكامن المحسوبة باستخدام طريقة بلاني كريدل المعدلة اعتمادا" على معطيات مناخية في منطقة اللاذقية لمدة 15عاما" (2001-2015) توضح النتائج أنه من خلال دراسة معامل الارتباط ومن خلال طبيعة توزع النقاط التجريبية حول المنحني المقارب الخطي, بأن صيغة تورك أعطت أفضل تقريب لصيغة بلاني كريدل المعدلة, بمعامل ارتباط (R=0.907) مقارنة" بصيغة تورنويت التي أعطت معامل ارتباط (R=0.846),أما بالنسبة لطريقة الحوض صنف آ كان معامل الارتباط (R=0.925) والتوزع جيد للنقاط التجريبية حول المنحني المقارب الخطي. بالتالي نستطيع ضمن ظروفنا التجريبية الاعتماد على صيغة تورك وطريقة الحوض صنف آ كأفضل تقريب لصيغة بلاني –كريدل المعدلة في تحديد الاحتياجات المائية للمحاصيل الزراعية في منطقة اللاذقية. The aim of this research is to simplify the methodof getting Evapotranspiration Potentielle (ETP) which forms the limit of water needs for crops . This was using done some experimental Equation like Turc formula and Thornthwaite formula (Thornthwaite, 1948) compared with the modified Blaney_ Criddle formula ( BlaneyCriddle , 1950) which is considered the basic formula in this research . Also , this research aims to find a formula enables us to use (Pans evaporation) method (class A) as a relative evidence to the need of watering in Lattakia by comparing it with the results of Evapotranspiration Potentielle which are calculated by the modified Blaney _Criddle method depending on climate data from Lattakia for fifteen years (2001 – 2015) . The results of studying the correlation coefficient and how the experimental points spread around the linear regression curve show that Turc gave the best approximaltion result to the developed Blaney – Criddle formula with correlation coefficient (R=0.907). After Turc formula there is Thornthwaite formula with correlation coefficient (R=0.846) . On the other hand Pan class A method gave approximal results to the developed Blaney–Criddle formula with correlation coefficient (R=0.925) and with good distribution of the experimental points around the linear regressions straight. So, in this study experimental conditions it could beased on Turc formula and Pan class A method as the best approximation to the developed Blaney- Criddle formula to define the water requirement of the agriculture crops in Lattakia.